The 678 Hz acoustic immittance probe tone: a more definitive indicator of PET than the traditional 226 Hz method - Justin M. Pyne; Tarek Ibrahim Lawen; Duncan D. Floyd; Manohar Bance (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The accurate diagnosis of Eustachian tube (ET) dysfunction can be very difficult. Our aim is to determine whether a 678 Hz probe tone is a more accurate indicator of Patulous ET (PET) than the 226 Hz probe tone when used in compliance over time (COT) testing. Methods Twenty subjects (11 normal ET ears and 7 PET ears) were individually seated in an examination room and connected to a GSI TympStar Middle Ear Analyzer. The order of probe tone frequency (678 or 226 Hz) was randomized. Baseline “testing” COT recordings for each ear undergoing testing were completed. Subjects were instructed to occlude their contralateral nostril and to breathe forcefully in and out through their ipsilateral nostril until the test had run to completion. This process was repeated with the probe tone that had not been previously run. For the control group, each subject had one random ear tested. For the experimental group, only the affected ear(s) was tested. Wilcoxon rank rum tests were performed to determine statistical significance. Results The baseline COT measurements for the control group and PET group were similar, 0.86 mL (SD = 0.34) and 0.74 (SD = 0.33) respectively. Comparing the 226 Hz tone between groups revealed that PET patients had a median COT difference 0.19 mL higher than healthy ET patients, and for the 678 Hz tone, PET patients had a median COT difference of 0.57 mL higher than healthy ET patients. Both were deemed to be statistically significant (p = 0.002, p = 0.004 respectively). The was a statistically significant median COT difference between the 678 Hz and 226 Hz of 0.61 mL (p = 0.034) for the PET group, while the same comparison for the control group of 0.05 mL was not significant (p = 0.262), suggesting that the 678 Hz tone yields a larger response for PET than the 226 Hz tone, and no difference for the control group, thus making it less prone to artifact noise interference. Conclusion The 678 Hz probe tone is a more reliable indicator of ET patency, and should be preferably used over the 226 Hz tone for future COT testing.